Pesticide exposome reveals oxidative stress and immune response disruptions in occupationally exposed women with breast cancer - Juliana Maria Bitencourt de Morais Valentim; Luciana Pizzatti; Carolina Coradi; Isabella Cristina Cazagranda; Bruna Fadel; Beatriz Geovana Leite Vacario; Shaiane Carla Gaboardi; Matheus Iago Oliveira Coletto; Rodrigo Kern; Wander Rogério Pavanelli; Daniel Rech; Maria Luiza Ferreira dos Santos; et al. (Scientific Reports)
Abstract Rural women are at a higher risk of developing breast cancer, but the molecular mechanisms involved remain poorly understood. This study investigates the impact of chronic pesticide exposure on systemic and tissue-level protein expressions in women diagnosed with breast cancer. Plasma and tumor samples were collected from 215 women diagnosed with breast cancer; among them, 128 patients were occupationally exposed (n = 128) and 87 patients were not occupationally exposed (87) were analyzed for further studies. High-throughput proteomic analyses of plasma revealed distinct protein expression profiles between the groups, primarily associated with inflammation, oxidative stress, and immune deregulation. Validation analysis showed that cytokines such as IL-1β, IL-12, IL-17A, and TNF-α were significantly reduced in both plasma and tumor samples from exposed patients compared to unexposed women. This reduction in cytokines, coupled with decreased tumor-infiltrating leukocytes (TILs) and CTLA-4 overexpression, suggests pesticide-induced immune compromise. Circulating IL-12 levels were significantly reduced in younger, eutrophic, and at menacme exposed patients. Pesticide exposure also influenced nitrosative stress production, leading to reduced NOx levels in plasma and impaired iNOS expression in TILs. These results suggest a potential link between pesticide exposure and the pathophysiology of breast cancer, offering new insights into the underlying molecular mechanisms.